DNA replication of single-stranded Escherichia coli DNA phages - Baas, P.D. (Elsevier, 1985)
Research on single-stranded DNA phages has contributed tremendously to our knowledge of several fundamental life-processes. The small size of their genomes and the fast rate at which they multiply in their host, Escherichia coil, made them attractive candidates for various studies. There are two classes of single-stranded DNA bacteriophages, which are denoted 'icosahedral' or 'isometric' and 'filamentous', based on the morphology of their representatives. Although an evolutionary connection between the two classes of phages may be inferred from the basically similar size, structure and organization of their genomes, there exist also a number of differences in the way both types of phages reproduce themselves.
Keywords: Biologie